2015
DOI: 10.1038/srep16282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced response inhibition in experienced fencers

Abstract: The inhibition of a prepotent response is an essential executive function which enables us to suppress inappropriate actions in a given context. Individuals with fencing expertise exhibit behavioral advantages on tasks with high demands on response inhibition. This study examines the electrophysiological basis for the superior response inhibition in experienced fencers. In the Go/Nogo task where frequent stimuli required a motor response while reaction had to be withheld to rare stimuli, the fencers, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 64 publications
5
35
0
Order By: Relevance
“…timing, behavioral effect, functional role, and anatomical feature (Bodmer, Muckschel, Roessner, & Beste, 2018;Miller, Ulrich, & Schwarz, 2009;Yang et al, 2017;D. D. Zhang, Ding, Wang, Qi, & Luo, 2015 (Fig 9d).…”
Section: Discussionmentioning
confidence: 97%
“…timing, behavioral effect, functional role, and anatomical feature (Bodmer, Muckschel, Roessner, & Beste, 2018;Miller, Ulrich, & Schwarz, 2009;Yang et al, 2017;D. D. Zhang, Ding, Wang, Qi, & Luo, 2015 (Fig 9d).…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned in the introduction, the NoGo-N2 reflects the inhibitory process of a motor plan prior to the motor execution stage (Eimer, 1993;Falkenstein et al, 1999;Herrmann et al, 2003;Karch et al, 2007;Kim et al, 2007;Huster et al, 2013), and this inhibitory process is usually located at the premotor level rather than at the motor level (Falkenstein et al, 1999). The N2 enhancement to the NoGo stimulus has been suggested to reflect the suppression of incorrect response prior to the motor action (Falkenstein et al, 1999;Zhang et al, 2015), and a shorter-latency NoGo-N2 has been observed in successful withholding to NoGo stimuli compared with unsuccessful attempts to inhibit (Roche et al, 2005). In addition, neuroimaging studies have revealed that the neural sources of NoGo-N2 are located in the ACC and inferior/orbitofrontal prefrontal cortex (Kiefer et al, 1998;Bokura et al, 2001;Bekker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prolonged NoGo-P3 latency might reflect the extent of evaluation processing (Roche et al, 2005). Taken together, the superior response inhibition in subjects was characterized by larger and shorter NoGo-N2 as well as smaller and shorter NoGo-P3 (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…timing, behavioral effect, functional role, and anatomical feature (Bodmer, Muckschel, Roessner, & Beste, 2018;Miller, Ulrich, & Schwarz, 2009;Yang et al, 2017;D. D. Zhang, Ding, Wang, Qi, & Luo, 2015).…”
Section: Discussionmentioning
confidence: 99%